Uses of the morpheme {-it-} in the colloquial Spanish of Lima - Quintanilla Anglas, Rómulo F. (2014)
{- it-} is a kind of derivative morpheme 'appreciative' type. The morphological studies of the Spanish language, is credited with semantic content related to the 'dimension' and 'emotional'. In this article we will give account of cases in which the mentioned morpheme is used to express value connotations which are not precisely the canonical described in studies of Spanish grammar. Possibly it is generalizing certain types of speakers trend factor that would encourage that these interact freely the mentioned morph with roots grammatically not usual and legislation considered incorrect. However, the semantic nuances that are used in the colloquial variety spoken in the city of Lima are a very productive communication resource, basically, in speakers that are in some way related to the quechua language. In this article we will give account of these uses, apparently it comes winning space in other areas of speakers.